2015
DOI: 10.4238/2015.june.18.27
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of S100P, CD147, and OCT4 in different prostate cancer tissue TNM stages

Abstract: ABSTRACT. The aim of this project was to investigate the expression and significance of S100P, CD147, and OCT4 in prostate cancer tissue at different TNM stages. We enrolled 54 patients with prostate cancer, 40 with benign prostatic hyperplasia, and 20 subjects with normal prostates. S100P, CD147, and OCT4 were detected by immunohistochemistry. The positive rate of S100P detection was 18.52% in prostate cancer tissues, significantly lower than in normal and benign prostate hyperplasia tissues (P ˂ 0.05). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Moreover, CD147 promotes proliferation, stimulates proteolytic enzyme expression, induces vascular endothelial growth factor expression and angiogenesis, and enables anchorage-independent growth (Bordador et al, 2000;Tang et al, 2005). For example, Wang et al (2015) reported that CD147 plays a role in proliferation, invasion, and chemosensitivity of the human gastric cancer cell line SGC7901. Therefore, a thorough understanding the CD147 biology and proteins interacting with BSG will have a significant impact on our understanding of the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CD147 promotes proliferation, stimulates proteolytic enzyme expression, induces vascular endothelial growth factor expression and angiogenesis, and enables anchorage-independent growth (Bordador et al, 2000;Tang et al, 2005). For example, Wang et al (2015) reported that CD147 plays a role in proliferation, invasion, and chemosensitivity of the human gastric cancer cell line SGC7901. Therefore, a thorough understanding the CD147 biology and proteins interacting with BSG will have a significant impact on our understanding of the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster of differentiation 147 (CD147) or extracellular matrix metalloproteinase inducer (EMMPRIN), also known as basigin (BSG), is a highly glycosylated transmembrane protein with increased expression in many forms of malignancy (Wang et al, 2015). CD147 induces the production of matrix metalloproteinases, a group of proteins that can degrade the extracellular matrix, in adjacent interstitial normal cells (Curran and Murray, 2000;Gabison et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 15 studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were identified for qualitative analysis. The study by Bauman et al was not included in the quantitative analysis because it provided the mean optical density of CD147 and not the positive expression rate of CD147.…”
Section: Characteristics and Risk Of Bias Of Included Studiesmentioning
confidence: 99%
“…The study by Bauman et al was not included in the quantitative analysis because it provided the mean optical density of CD147 and not the positive expression rate of CD147. Therefore, 14 studies [ 9 , 10 , 11 , 12 , 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were included for quantitative analysis, including 12,591 prostate cancer tissues, 298 benign prostatic hyperplasia tissues, and 175 normal prostate tissues. Six articles provided a positivity rate of CD147 expression in prostate cancer and normal prostate tissues, 8 articles reported on CD147 expression in prostate cancer and benign prostatic hyperplasia, 12 articles involved Gleason score, 6 articles involved TNM stage, 5 articles involved differentiation, 6 articles involved lymph node metastasis, and 2 articles involved distant metastasis.…”
Section: Characteristics and Risk Of Bias Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation